Building an open-source community to enhance autonomic nervous system signal analysis: DBDP-autonomic - Dunn, Jessilyn; Mishra, Varun; Shandhi, Md Mobashir Hasan; Jeong, Hayoung; Yamane, Natasha; Watanabe, Yuna; Chen, Bill; Goodwin, Matthew S. (Frontiers in Digital Health, 2025)
Smartphones and wearable sensors offer an unprecedented ability to collect peripheral psychophysiological signals across diverse timescales, settings, populations, and modalities. However, open-source software development has yet to keep pace with rapid advancements in hardware technology and availability, creating an analytical barrier that limits the scientific usefulness of acquired data. We propose a community-driven, open-source peripheral psychophysiological signal pre-processing and analysis software framework that could advance biobehavioral health by enabling more robust, transparent, and reproducible inferences involving autonomic nervous system data.